Bacterial Fucose-Rich Polysaccharide Stabilizes MAPK-Mediated Nrf2/Keap1 Signaling by Directly Scavenging Reactive Oxygen Species during Hydrogen Peroxide-Induced Apoptosis of Human Lung Fibroblast Cells - Roy Chowdhury, Sougata; Sengupta, Suman; Biswas, Subir; Sinha, Tridib Kumar; Sen, Ramkrishna; Basak, Ratan Kumar; Adhikari, Basudam; Bhattacharyya, Arindam (PLOS ONE, 2014)
Continuous free radical assault upsets cellular homeostasis and dysregulates associated signaling pathways to promote stress-induced cell death. In spite of the continuous development and implementation of effective therapeutic strategies, limitations in treatments for stress-induced toxicities remain. The purpose of the present study was to determine the potential therapeutic efficacy of bacterial fucose polysaccharides against hydrogen peroxide (H2O2)-induced stress in human lung fibroblast (WI38) cells and to understand the associated molecular mechanisms. In two different fermentation processes, Bacillus megaterium RB-05 biosynthesized two non-identical fucose polysaccharides; of these, the polysaccharide having a high-fucose content (∼42%) conferred the maximum free radical scavenging efficiency in vitro. Structural characterizations of the purified polysaccharides were performed using HPLC, GC-MS, and 1H/13C/2D-COSY NMR. H2O2 (300 µM) insult to WI38 cells showed anti-proliferative effects by inducing intracellular reactive oxygen species (ROS) and by disrupting mitochondrial membrane permeability, followed by apoptosis. The polysaccharide (250 µg/mL) attenuated the cell death process by directly scavenging intracellular ROS rather than activating endogenous antioxidant enzymes. This process encompasses inhibition of caspase-9/3/7, a decrease in the ratio of Bax/Bcl2, relocalization of translocated Bax and cytochrome c, upregulation of anti-apoptotic members of the Bcl2 family and a decrease in the phosphorylation of MAPKs (mitogen activated protein kinases). Furthermore, cellular homeostasis was re-established via stabilization of MAPK-mediated Nrf2/Keap1 signaling and transcription of downstream cytoprotective genes. This molecular study uniquely introduces a fucose-rich bacterial polysaccharide as a potential inhibitor of H2O2-induced stress and toxicities.